The Practicality of Electronic Student Worksheets (E-LKPD) Based on Project-Based Learning for Biotechnology Material - Simamora, Jenny Br; Hajar, Ibnu (Universitas Negeri Semarang, 2025)
The integration of Project Based Learning (PjBL) in science education, particularly in biotechnology, is essential to foster students' critical thinking, collaboration, and problem-solving skills. However, many learning materials, especially student worksheets, often remain conventional and lack digital adaptation, making them less engaging and less practical for classroom implementation. This study aims to determine the practicality of electronic student worksheets based on Project Based Learning for biotechnology material for class X.3 of SMA Negeri 1 Kampar Kiri Hilir and SMA Negeri 1 Kampar Kiri. This study is a quantitative descriptive study. Data collection was carried out using interviews, observations, questionnaires and documentation. The sample in this study was 56 students. The research method used was the Research and Development (R&D) development method with the Plomp model. Data collection was taken in 2 meetings on biotechnology material. The instruments used in this study were student, teacher and observer practicality questionnaires and implementation questionnaires that measured the overall learning activities carried out. In the student practicality questionnaire in both schools, the score was (85.5%) in the very practical category and the teacher practicality questionnaire in both schools had a score of (88.75%) in the very practical category. In the practicality questionnaire, observers in both schools had a value of (94%) with a very practical category. In the questionnaire, the implementation of learning activities in both schools had a value of (98%) with a category that was implemented overall. From the results of the study, it can be concluded that the Student Worksheet based on Project Based Learning Material Biotechnology is practical and implemented overall in class X students of SMA Kampar Regency.